A study of cultural intelligence on job stress for global employees. - Chia, Geraldine Yi Yun. (2010)
Drawing upon the Job Demand-Resource (JDR) and Conservation of Resource (COR) models of stress, our paper examines the effects of job demands and cultural intelligence (CQ) on job stress in the context of global employees. In addition, we also tested for the moderating effects of the four dimensions of CQ (metacognitive, cognitive, motivational and behavioral) on the job demand-job stress relationship. This paper will contribute to emerging research on CQ by exploring CQ of global employees. As global employees have to confront additional job stress from an unfamiliar culture in their new working environments, we argue that their personal attributes of CQ would serve as resources to help buffer the job stress they experience. Regression analysis results of a survey of 216 global employees, showed a significant relationship between motivational CQ and job stress. Lastly, we discussed theoretical implications on global employees’ stress literature and practical suggestions were made in relation to alleviating global employees’ job stress on overseas assignments.